Strengthening Literacy Through Project-Based Learning (PjBL) by Ethnostories-Based Gumansalangi Story Comics Making at the Indonesian Schools of Davao, Philippines - Riski, Yunia Tiara; Huda, Muhammad Nur (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research aimed to strengthen the literacy of Indonesian School of Davao (SID) students through the Project Based Learning (PjBL) model by creating ethnostories-based comics Gumansalangi Stories. Considering that most SID students face challenges in mastering Indonesian, this research seeks to develop literacy skills with methods that are interesting and relevant to their culture. The research method used is descriptive with observation techniques, interviews and analysis of student project results. The research subjects consisted of Phase C students (grades V and VI). The learning process was carried out according to PjBL syntax, which involved project planning stages, data collection, digital comic preparation, and results evaluation. The research results showed that the use of PjBL in making comics based on the Gumansalangi Story is effective in increasing student literacy. Based on the evaluation, students scored 75% in story idea creativity, 50% in word productivity, and 63% in story line structure. These results showed that students had a good understanding of the material and were able to compose stories in an interesting and coherent manner. It was concluded that the application of PjBL in making ethnostories-based comics can improve students' literacy skills, both in the aspects of reading and writing. In addition, this approach helps preserve local culture and strengthen students' identity as part of the Indonesian nation. This research recommends further studies to further develop technology and culture-based literacy methods.